2019
DOI: 10.30954/0424-2513.3.2019.22
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Growth and Instability of Groundnut Production in Karnataka: Evidence from Hazel’s Decomposition Model

Abstract: The study conducted in Karnataka state with an objective to find out the sources of growth and instability of groundnut production. The CAGR, CDI and Hazel's decomposition model was used. The growth pattern showed a downward trend along with higher instability in area, production and yield of groundnut in all the districts during period II. The variation in groundnut production was predominantly due to interaction effect of yield and area during period I, whereas change in mean area largely contributed during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Ramesh and Raju (2009) said that oilseed production is found more risky as compared to cereals and pulses. Jainuddin et al (2019) reported that the growth pattern of groundnut indicated a downward trend especially during period II in Karnataka state. The high degree of instability in oilseeds production leads to large gap between consumption and production of edible oils in our country.…”
Section: Programmes and Schemes Governing Edible Oilseeds And Oils Inmentioning
confidence: 99%
“…Ramesh and Raju (2009) said that oilseed production is found more risky as compared to cereals and pulses. Jainuddin et al (2019) reported that the growth pattern of groundnut indicated a downward trend especially during period II in Karnataka state. The high degree of instability in oilseeds production leads to large gap between consumption and production of edible oils in our country.…”
Section: Programmes and Schemes Governing Edible Oilseeds And Oils Inmentioning
confidence: 99%
“…However, analyzing the trends of growth and variability in agricultural production and the sources of its variability is important to formulate appropriate policies and strategies that can enhance sustainable agricultural production and develop a reliable future projection ( Deb and Soumitra, 2015 ). Due to this, several studies ( Pattnaik and Shah, 2015 ; Sharma et al., 2017 ; Jainuddin et al., 2019 ; El-Rasoul et al., 2020 ; Ikuemonisan et al., 2020 ) examined the trends in production growth and variability of various crops in various parts of the world. The present study is, hence, aimed at estimating the growth rate and instability in harvested area, production, and productivity of coffee, and examining the contributions of harvested area and productivity and their interaction to the growth of coffee production in Ethiopia in the entire (1993–2019), pre-AGP (1993–2010) and AGP (2011–2019) periods.…”
Section: Introductionmentioning
confidence: 99%